Chapter 13: Heat - Saifful Kamaluddin, Muzakir (SAP Publications Sdn. Bhd., 2011)
Heat transfer is a discipline that concerns the transfer of thermal energy. There are several ways heat can be transferred from a system to another. Basically, heat will be transferred from a higher temperature system to a lower temperature system. This chapter discusses the rate of transfer and thermal expansion due to heat transferred.